Rain events and recharge processes in the San Luis Valley of Southern Colorado - Lanzoni, M (2019)
Many drylands around the world are dependent on high-elevation snowmelt for aquifer recharge. Much of the groundwater in the American West relies on precipitation formed in the Rocky Mountains. Understanding how snowmelt-driven recharge may change over time is an important component to sustainably managing these groundwater resources. The San Luis Valley of southern Colorado is the highest elevation area in the United States used for industrial agriculture. Precipitation on the valley floor is 200 mm/yr, but its water resources are sustained by precipitation > 1,000 m higher in the San Juan and the Sangre de Cristo Mountains, at the southern extent of the Rocky Mountains.